BEREAKSI: PENDAMPINGAN IMAN KELUARGA DI PAROKI ST. PAULUS LAMBING, KALIMANTAN TIMUR - Prasetyantha, Y. B.; Nggajo, Irenius; Pratama, Vallian Yoga; Sesar, Dominikus Mario Dola; Rengga, Stefanus (Universitas Sanata Dharma, 2025)
Faced with the limited pastoral services intertwined with the need for basic faith education in families in St. Paulus Lambing Parish, West Kutai, this community service offers a collaborative and integral family faith accompaniment for parents, young people, and children. The team came to the location, lived, and did activities with the community, especially in the four service center stations in this Parish. During the live-in, the team carried out seven activities packaged with the BEREAKSI method, which elaborated aspects of playing/learning, reflection, and concrete action. This service received an enthusiastic response from the community, from parents, young people, and children. The activity materials, which were appropriate for ages and methods and involved the minds, hearts, and selves of the participants, received appreciation because they answered the longings and needs of the community. In particular, this community service was beneficial for parents to deepen their understanding of the four roles of the family according to Familiaris Consortio and the richness of the seven sacraments in the Church, for young people to recognize their identity and calling as people loved by God, and for children to recognize and love the basic prayers in the Catholic Church.